SAT0028 Systemic sclerosis – effects of agonistic auto-antibodies directed against the angiotensin receptor type 1 and the endothelin receptor type a on immune cells. (23rd January 2014) - Guenther, J.; Becker, M.O.; Kill, A.; Riemekasten, G.
Abstract : Background: Autoimmunity, vasculopathy and fibrosis are features of Systemic Sclerosis (SSc). The functional link between these three pathophysiological components is still missing. Research suggests an involvement of endothelin-1 and angiotensin II, and of the activation of their receptors by the natural ligands as well as by agonistic autoantibodies against these receptors in SSc–associated vasculopathy and fibrosis. Objectives: We found auto-antibodies against the angiotensin receptor type 1 (AT1R) and the endothelin receptor type A (ETAR) in SSc patients sera [1]. Additional we proved the expression of these receptors on peripheral immune cells. Now we investigate the effects of these auto-antibodies on human immune cells, the association with clinical data and their possible role in the pathogenesis of Systemic Sclerosis. Methods: Peripheral blood mononuclear cells (PBMCs) from healthy donors were isolated by gradient centrifugation and in vitro stimulated by affinity-purified IgG from sera of SSc patients containing anti-AT1R and anti-ETAR antibodies as well as by affinity-purified IgG from sera of healthy donors. After stimulation the expression of activation markers and cytokines were measured by flow cytometry or ELISA. Results: Stimulation of PBMCs by SSc patients IgG resulted in a significantly increased expression and secretion of IL-8 and an abundant but due to a broad range not significant secretion of CCL18 compared to the stimulation by IgG of healthy donors. These effects were blocked by commercial AT1R and ETAR antagonist, confirming the specifity of the biological activity of the auto-antibodies. Correlation analysis with clinical data of the SSc patients whose IgGs were used revealed a negative correlation of IL-8 expression with the time since onset of SSc features like Raynaud phenomenon and skin fibrosis, and an association of CCL18 expression with the incidence of vascular complications. The analysed surface activation markers were not or only slightly increased. Conclusions: SSc patient IgGs containing anti-AT1R and anti-ETAR antibodies seem to have effects on inflammation immune regulation and fibrosis. IL-8 is a major inflammatory cytokine and CCL18 is a fibrotic cytokine. Both are mainly secreted by monocytes among the peripheral immune cells and are chemoattractants especially for T cells and monocytes/macrophages. IL-8 may play an important role particularly in the early stage of SSc contributing to leucocyte infiltration, vascular inflammation and injury, which are regarded to be the first events leading to tissue damage and fibrosis. CCL-18 is known to be a fibrotic cytokine, also contributing to leucocyte infiltration, and known to be involved in pulmonary fibrosis in SSc and other diseases. Here we could show that anti-AT1R and anti-ETAR auto-antibodies from SSc patients have effects on inflammation, immune regulation and fibrosis via the induction of IL-8 and CCL18 secretion by monocytes. Therefore these auto-antibodies could be the link between autoimmunity, vasculopathy and fibrosis. The signaling needs to be further investigated. References: Riemekasten et al., 2011. Involvement of functional autoantibodies against vascular receptors in systemic sclerosis, Ann Rheum Dis. 2011 Mar;70(3):530-6, PMID: 21081526 Disclosure of Interest: None Declared